2018
DOI: 10.1177/0956797618798620
|View full text |Cite
|
Sign up to set email alerts
|

Income Inequality Affects the Psychological Health of Only the People Facing Scarcity

Abstract: Following the status-anxiety hypothesis, the psychological consequences of income inequality should be particularly severe for economically vulnerable individuals. Oddly, however, income inequality is often found to affect vulnerable low-income and advantaged high-income groups equally. We argue that economic vulnerability is better captured by a financial-scarcity measure and hypothesize that income inequality primarily impairs the psychological health of people facing scarcity. First, repeated cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 36 publications
3
52
0
1
Order By: Relevance
“…Of 15 studies that were only partially supportive of the IIH, reasons for this included associations only being seen: in low-income participants or deprived wards [ 67 , 68 , 86 ], with respect to certain symptoms or presentations [ 70 , 71 , 75 , 81 , 85 ], prior to adjustment for covariates [ 84 , 88 , 89 ], in women [ 78 ], at the provincial but not county level [ 87 ], at a given time-lag [ 79 ]. Finally, one study found that inequality predicted variance in depression symptoms between but not within twin pairs [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of 15 studies that were only partially supportive of the IIH, reasons for this included associations only being seen: in low-income participants or deprived wards [ 67 , 68 , 86 ], with respect to certain symptoms or presentations [ 70 , 71 , 75 , 81 , 85 ], prior to adjustment for covariates [ 84 , 88 , 89 ], in women [ 78 ], at the provincial but not county level [ 87 ], at a given time-lag [ 79 ]. Finally, one study found that inequality predicted variance in depression symptoms between but not within twin pairs [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, 33.33% (n = 14) of the studies were unsupportive of either hypothesis [95][96][97][98][99][100][101][102][103][104][105][106][107][108], three of which (21.43%) showed mixed findings [98,104,107] and the remaining 11 (78.57%) reporting only null findings. Of 15 studies that were only partially supportive of the IIH, reasons for this included associations only being seen: in low-income participants or deprived wards [67,68,86], with respect to certain symptoms or presentations [70,71,75,81,85], prior to adjustment for covariates [84,88,89], in women [78], at the provincial but not county level [87], at a given time-lag [79]. Finally, one study found that inequality predicted variance in depression symptoms between but not within twin pairs [82].…”
Section: Findings Based On All Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Elgar et al, 2013) supported the psychosocial explanations linking subjective SES with health outcomes. Such comparative explanations take into consideration the effects of the macro contexts and propose that income inequalities in the society are likely to enhance feelings of relative deprivation and impair psychological health of those facing scarcity (Sommet, Morselli & Spini, 2018). The effects of income inequality in the society on individuals' perceptions of their personal and group-level wealth has been demonstrated with cross-sectional international data (with data from World Values Survey), longitudinal data (with data from Swiss Householf Panel; see Sommet et al, 2018) and experimentally (with samples from Spain, Australia, and USA; see Sanchez-Rodriguez et al, 2019).…”
Section: Effects Of Socioeconomic Status On Health and Well-beingmentioning
confidence: 99%
“…On the one hand, the impact on people's well-being has been studied by taking into consideration the material conditions or the objective SES (OSS) in which they live (Tay & Diener, 2011) which refers to the capability to cover their basic needs (i.e., food, shelter, heat). These material conditions are predictors of psychological well-being (Diener & Oishi, 2000), especially among those who face scarcity in unequal contexts (Sommet, Morselli, & Spini, 2018). On the other hand, well-being has been studied by using the relative conditions or the subjective SES (SSS; Adler, Epel, Castellazzo, & Ickovics, 2000) that lead people or groups to (up or down) social comparisons with other individuals or groups within their society.…”
mentioning
confidence: 99%